Study on Total Loss in Distribution Transformer of Junction at Khouathi 1 And Sansouk Substation - SAYPASERTH, Phetsadachanch; VANG, Neng (Souphanouvong University Journal Multidisciplinary Research and Development, 2017)
Current power is essential factor for developing nations, particularly in communications, telecommunications, education, development of industrial technology as well as live everyday people of the state enterprises power, it supply power to the extent of using power-supply power certainly less Must give injections and enough demand, but some problems cannot risk transport of energy in particular are losing the power loss is loss techniques and Non- techniques such as: Power loss in techniques losses include: loss of transmission, loss of transformers and power losses in fire extinguishers, Power loss in Non-technical losses due to: people stealing, current leaks. So, The Lao Electric Power Corporation or EDL has paid attention to this problem because of this loss of power, which is a major problem and the annual loss of Lao electricity industry revenues. Through a studies of the power lost in the Power Transformer in Sansouk Substation and Khouathi 1 Substation it’s been installed the Transformer with 20 - 2000 kVA in each transmission line and the power loss it can be summarized as follows: Sansouk Station: Loss in station is 103 kW and Loss of Analyze is 129 kW. Khouathi 1 station: Loss in station is 173 kW and Loss of Analyze is 180 kW. In loss of power in the Transformer, it is seen as close to the real loss of actual analysis in the Substation